RESILIENSI EKONOMI MASYARAKAT DESA WISATA PENGLIPURAN DI TENGAH PANDEMI COVID-19 - Ida Bagus Putra Negarayana (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Penglipuran Tourism Village feels the negative impact of the Covid-19 pandemic on its tourism activities. Before the pandemic, the rapid tourism activity in Penglipuran Tourism Village made many rural communities dependent on the tourism sector. However, due to the prolonged pandemic, many people have to change professions to be able to survive and the economy can not run properly. Therefore, this study aims to analyze the economic resilience of the local community of Penglipuran Tourism Village in the midst of the Covid-19 pandemic. This study uses quantitative and qualitative methods (Mix Method). The study showed that the economic condition of the Penglipuran Tourism Village Community experienced a decline in the midst of the Covid-19 Pandemic, this was influenced by several things, namely the decline in tourism activities in the village due to restrictions on activities and government policies, livelihood sources that changed for the worse and a decrease in income and public spending. The Economic Resilience of the Penglipuran Tourism Village Community is carried out in tourism activities by implementing the CHSE health protocol, village promotion, and village planning through improvements and additions to facilities and infrastructure support livelihood resilience efforts are carried out by digitizing products with online promotions, as well as the existence of delivery services that benefit buyers, the role of the government in resilience is to provide direct cash assistance to the community.